Strategi revitalisasi wisata pulau :: Studi kasus Pulau Kotok Besar Kepulauan Seribu - ACHYARUDDIN, ACHYARUDDIN ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This study has two aspects to be examined/analyzed, namely: (1) the tourism development of Kotok Besar Island, (2) environmental conservation efforts on Kotok Besar Island. The aim of this study is to (1) determine the factors that lead to stagnation and even the declining trend associated with the development of tourism on the Kotok Besar Island to further identify and identify key factors that can affect the success of the tourism development of the island (island tourism) on Kotok Besar Island, (2) determine sustainable tourism development strategy of the island (island tourism) on Kotok Besar Island. Research method uses qualitative description. The data collection is conducted by interview and observation (field survey and secondary data) about (1) the development of tourism in the Kotok Besar Island, namely tourism products that include attractions, amenity, accessibility, (2) environmental conservation efforts on Kotok Besar Island, which includes quality of experience, quality of resources, and quality of the local people. Structured interviews conducted on the Regional Government of DKI Jakarta (Jakarta Tourism Board), the private sector (resort manager), the conservation of nature (the manager of the National Institute for Marine Parks of the Thousand Islands and manager of Elang Bondol Breeding Conservation), and the local community. Field observation survey is conducted by street survey. Results from this study indicate that tourism development on Kotok Besar Island is stagnant and even declining. This condition is caused by (1) product management factor that has not been managed in an integrated manner, (2) factors of cooperation, coordination and communication between related stakeholders (Provincial Government of DKI Jakarta, private sectors, NGO, volunteers, local communities) which are not synergistic, (3) conditions of nature (sea, beaches), flora and fauna on the Kotok Besar Island are starting to be endangered.